PENGARUH VIRAL MARKETING TERHADAP JUMLAH KUNJUNGAN WISATAWAN INDONESIA KE KOREA SELATAN - Isawatul Jariah, Akbar; Sasrawan Mananda, I GPB.; Sudiarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 6 No 1 (2018): Jurnal IPTA (July 2018)DO - 10.24843/IPTA.2018.v06.i01.p02, 2018)
The aim of this research is to find out how big the influence of viral marketing that has elements of information spreading, credibility of information, expressing positive feelings, economic incentive, and helping the company towards the number of Indonesian tourists visit to South Korea, Sample determination in this study using accidental sampling method with a total of 100 respondents. Data collection techniques used questionnaires, nonparticipation observations, interviews, and literature. Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, validity and reliability test, hypothesis test, and coefficient of determination analysis using SPSS version 17.0. The results of this study indicate the influence of viral marketing towards the number of Indonesian tourists visit to South Korea is very significantly simultaneous and partial effect with a value of 91,6%. For the economic incentive dimension, the result of analysis is 3,705, helping the company 3,311, credibility of information 2,461, information spreading 2,220, and expressing positive feelings 2,020. The data collected through online questionnaires to the respondents who have ever visited South Korea.